Lectin-Recognizable MOF Glyconanoparticles: Supramolecular Glycosylation of ZIF-8 Nanocrystals by Sugar-Based Surfactants - Gimenez, Rodrigo Esteban (2019)
A strategy toward the integration of highly functional microporous materials, such as metal-organic frameworks (MOFs), in composites via biochemical recognition interactions is presented. Postsynthetic modification of zeolitic-imidazolate framework-8 MOF nanocrystals with a maltose-exposing biocompatible surfactant (the socalled “Glyco-MOFs”) was performed to confer affinity toward lectin protein concanavalin A. The addition of small amounts of concanavalin A to the colloidal Glyco-MOF dispersion triggers the aggregation of these units into self-limited size supramolecular architectures directed by specific sugar−lectin binding interactions.